Farmers Adaptation of Post Conversion Land in Subang District, West Java, Indonesia - Paulus Basuki Kuwat Santoso; Widiatmaka Widiatmaka; Supiandi Sabiham; Machfud Machfud; I Wayan Rusastra (Wacana Journal of Social and Humanity Studies, 2018)
Subang Regency has an important role as the rice supplier area. As one of the rice production centers in Indonesia, rice farmers address rice fields as an asset or resource. As an asset, farmers conduct rice farming activities in the rice fields with economical orientation and rely on their food source mainly from the rice production. Conversions of paddy fields have changed the socioeconomic balancing amongst the farmers. They responded to the changes by adapting to new conditions, thus farmers’ post-conversion responses are an interesting aspect to study. This research aimed to understand the rice farmers adaptations, which was involved 15 key informants using in-dept interviews and purposive sampling method of 164 respondents. The analysis of the interview results used the concept of adaptation based on objectives, timing, and then strengthened with relevant documents for the study area. This study found, that: 1) farmers tried to make adjustments in using the compensation funds, livelihood, professions, farming, and household needs; 2) farmers’ adaptation are their way to earn the income and maintain their livelihood, and 3) some farmers firmly stated that their adaptations have made newly more prosperous conditions for them.